Water crisis in the Eastern Hindu Kush: a micro-level study of community-based irrigation water management in the mountain village Kushum, Pakistan - Ahmad, Zahir; Fazlur-Rahman,; Dittmann, Andreas; Hussain, Kamal; Ihsanullah, I. (ERDKUNDE, 2020)
Irrigation water scarcity is a rapidly growing problem in the Hindu Kush-Karakorum-Himalayan region. Water is depleting and becoming scarce around the world due to a lack of integrated water management. Researchers have focused on sophisticated irrigation water management systems as an integral strategy to address water scarcity. However, rapid population growth, climate variability, and changes in mountain regions are exerting increasing pressure on water resources. To cope with water scarcity situations, local communities have developed sustainable management mechanisms throughout the mountain regions of the world. These practices are considered as adaptive strategies to address scarcity situations. This article aims to explore the multi-stage, spatio-temporal indigenous appropriation mechanisms of irrigation water and to analyze the seasonal variation in water entitlements in a semi-arid mountain milieu, i.e., Kushum-Chitral. This study is based on a decade of research conducted in the study area. Data were collected in four phases from 2010 to 2018. The study indicates that the share of co-owners has decreased substantially over time due to demographic development and climate change but does not always lead to the tragedy of commons. The study reveals that the local communities have the capacity and capability to sustainably manage an important and scarce resource – i.e., irrigation water – without external intervention.